Appraisal of hydrogeological status from the apex of a propagating delta front: a real-time survey at Namkhana block, Sundarban biosphere reserve, India - Uddipan Das; Susanta Chaudhuri; Bijay Halder; Miklas Scholz (Discover Sustainability)
Abstract To ascertain the groundwater physicochemical quality and spatiotemporal variation, a systematic real-time hydro-geological field survey was conducted across 22 bore wells during both the Pre-Monsoon (PrM) and Post-Monsoon (PoM) seasons of 2022, in the Namkhana Development Block, South 24 Parganas, a significantly populated area of the Sundarban Biosphere Reserve (SBR). Hydrochemical analysis assessed its viability for drinking, domestic, and irrigation. The spatiotemporal fluctuation of cations and anions was portrayed by the concentration contour diagrams along with standard statistical approaches like correlation analyses and PCA to ascertain the interdependence between the major ions. Relevant plots and standard formulae were inculcated to evaluate the groundwater’s appropriateness for drinking and irrigation. Findings revealed a strong interdependence between EC, TDS, and Na+, whereas pH exhibited negligible influence. The dominant cation and anion sequence for both the PrM and PoM was (Na+ > Ca2+ > Mg2+ > K+) and (HCO3 − > Cl− > SO4 2− > NO3 −). Higher concentrations of Na+ and Cl− in coastal areas decreased inland, highlighting the effects of salt intrusion. Overall, the suitability of groundwater for agricultural, drinking, and domestic uses also varies adversely from its normal acceptable limits. Excessive and unregulated tapping of groundwater from the deeper aquifers for irrigation to meet the required yield seems to be the key reason for depleted water quality in the area. The findings underscore the importance of ion interactions and saline water intrusion in defining the groundwater situation in this region. The research output provides an updated hydrogeological status of the Block, useful for better water management plans relevant to public health engineering and irrigation.